METODE KRITIK MATAN HADIS PERSPEKTIF ULAMA HADIS - Akbari, Muhammad Fikri; Hudaya, Hairul; Munawwarah, Hafizhatul (STAI AL FALAH Banjarbaru, 2025)
Hadith scholars agree that the validity of hadith is not only determined by the quality of sanad but also matan. Sanads that have authentic quality are not necessarily also valid eyes. This has implications for the quality of the hadith itself. Therefore, it is important to know how scholars criticize the quality of hadith. This article aims to find out the criticism of matan hadith from the perspective of hadith scholars. This research is a literature review with a qualitative descriptive approach. Data related to the criticism of matan hadith are extracted from the book of hadith science which is then classified and analyzed with content analysis. Research found that criticism of matan is done by comparing hadith with the Qur'an, comparing several hadith histories, comparing hadith with other sciences and examining the linguistic aspects of hadith.Keywords: Criticism Of Matan, Quality Of Hadits, Quality Of Sanad.Ulama hadis sepakat bahwa kesahihan hadis tidak hanya ditentukan oleh kualitas sanad namun juga matan. Sanad yang berkulitas sahih belum tentu matannya juga sahih. Hal ini berimplikasi pada kualitas hadis itu sendiri. Karena itu, penting untuk mengetahui bagaimana kritik ulama terhadap kualitas hadis. Artikel ini bertujuan untuk mengetahui kritik matan hadis dari perspektif ulama hadis. Penelitian ini merupakan kajian literatur dengan pendekatan deskriptif kualitatif. Data terkait dengan kritik matan hadis digali dari kitab ilmu hadis yang kemudian diklasifikasikan dan dianalisis dengan content analisis. Penelitian menemukan bahwa kritik terhadap matan dilakukan dengan cara membandingkan hadis dengan Alquran, membandingkan beberapa Riwayat hadis, membandingkan hadis dengan ilmu lain dan meneliti aspek kebahasaan hadis. Kata Kunci: Kritik Matan, Kualitas Hadits, Kualitas Sanad.